Apostasy and Jewish identity in High Middle Ages Northern Europe : 'are you still my brother?' - Goldin, Simha (Manchester : Manchester University Press, 2014)
The attitude of Jews living in the medieval Christian world to Jews who converted to Christianity or to Christians seeking to join the Jewish faith reflects the central traits that make up Jewish self-identification. The Jews saw themselves as a unique group chosen by God, who expected them to play a specific and unique role in the world. This study researches fully for the first time the various aspects of the way European Jews regarded members of their own fold in the context of lapses into another religion. It attempts to understand whether they regarded the issue of conversion with self-confidence or with suspicion, and whether their attitude was based on a clear theological position, or on issues of socialisation. The book will primarily interest students and lecturers of Jewish/Christian relations, the Middle Ages, Jews in the Medieval period, and inter-religious research.
Apostasy and Jewish identity in High Middle Ages Northern Europe: 'Are you still my brother?'; Half Title Page; Title Page; Copyright; Contents; Preface; Leading figures; Abbreviations; 1. Early beginnings; 2. Forced conversion during the First Crusade; 3. Theological confrontation with Christianity's success; 4. Self-definition and halakhah; 5. Attitudes towards women; 6. Alternative perspectives: The literature of pietists (Ashkenazic hasidim); 7. Converts to Judaism; 8. Conclusions: The change in mentality; Bibliography; Index
Description based on online resource; title from PDF title page (EBSCO, viewed December 30, 2015).
Includes bibliographical references and index.
Master record variable field(s) change: 072
Keywords: Jews -- Europe, Northern -- History -- To 1500.; Judaism -- Relations -- Christianity -- History -- To 1500.; Christianity and other religions -- Judaism -- History -- To 1500.; Jews -- Identity; Europe, Northern -- Ethnic relations -- History -- To 1500.; SOCIAL SCIENCE / Discrimination & Race Relations; SOCIAL SCIENCE / Minority Studies; Christianity; Ethnic relations; Interfaith relations; Jews; Jews -- Identity; Judaism; Europe, Northern; European history; History; Humanities; Regional and national history; To 1500; Electronic books; History